Japan’s Sharp Corporation: Aiming to boost its competitive edge (B) - SRIKANTH, Kannan (Institutional Knowledge at Singapore Management University, 2020)
Set in January 2020, this case describes the entrepreneurial journey of Hayman Microfinance (Hayman), which provided financial solutions to the low-income strata and rural population of Myanmar who had limited or no access to banking services. Over 2015-2020, Hayman grew to become a 25-branch strong company with a loan portfolio of US$29 million, 129,000 active borrowers, and 155,000 depositors. Besides its product attributes, targeted marketing approach, trained work force and effective delivery, Hayman’s success could also be attributed to its corporate social responsibility (CSR) thrust in the areas of health, education, safety, and the environment. Over 2017-2019, many international players had entered Myanmar. While some of these entrants had big spending budgets, they lacked first-hand experience of the country’s rural poor, and had limited knowledge of the demanding bureaucratic processes followed by the Myanmar government in the financial sector. Sultan Marenov, the Executive Chairman and Managing Director of Hayman, believed that Hayman would be an ideal partner for such investors; however, he was yet to clinch a satisfactory deal. Would highlighting Hayman’s CSR program as a core element of its business model strengthen the company’s value proposition to potential investors? How much did the social activities contribute towards building the company’s brand equity among its key stakeholders, and a sustainable competitive advantage? Students will learn to analyse the attractiveness of microfinance industry in an under-developed market, and the role played by different stakeholders. They will also get to evaluate the potential of CSR as a core element of a company’s business model and as a key resource for creating sustainable competitive advantage. In addition, the case discussion will highlight the significance of measuring social impact in quantitative metrics and demonstrate how analytical tools can be used for the same.